2000
DOI: 10.1080/08870440008405578
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and self efficacy beliefs in adolescents and young adults with insulin dependent diabetes mellitus

Abstract: The study examined the role of illness perceptions and self-efficacy in diabetic regimen adherence and metabolic control among young patients with Insulin Dependent Diabetes Mellitus (IDDM). Sixty-four outpatients with Insulin Dependent Diabetes completed measures of illness perceptions, generalised and diabetes specific selfefficacy and a self-report measure of adherence. Metabolic control (HbAlc) was also assessed. Control, identity and consequences components of illness perceptions were significantly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
154
0
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(179 citation statements)
references
References 80 publications
10
154
0
13
Order By: Relevance
“…The value of self-efficacy in predicting self-care behaviors and outcomes in patients with diabetes is supported by several studies, in which self-efficacy was associated with self-reported adherence in adults (3)(4)(5)(6)(7)(8)(9) and adolescents (10,11), glycemic control (8,12,13), and better perceived general health, mental health, and social functioning (14).…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…The value of self-efficacy in predicting self-care behaviors and outcomes in patients with diabetes is supported by several studies, in which self-efficacy was associated with self-reported adherence in adults (3)(4)(5)(6)(7)(8)(9) and adolescents (10,11), glycemic control (8,12,13), and better perceived general health, mental health, and social functioning (14).…”
mentioning
confidence: 78%
“…Although self-efficacy is not the only explanatory factor, it can add substantially to our understanding of self-care behavior: whereas self-judgements of efficacy may not presume individuals readiness to follow treatment recommendations, they must be present for treatment adherence to occur (13). Enhancing self-efficacy may increase patients' motivation for-and success with-behavioral efforts.…”
Section: Study 2: Test-retest Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…12 The IPQ 11 has been utilised in studies examining patients' adaptation to various conditions, such as heart disease, 13 rheumatoid arthritis, 14 chronic fatigue syndrome 15 and diabetes. 16 The IPQ subscales demonstrated good internal and test-retest reliability and good discriminant, construct and predictive validity. 12 For this study, items were modified to be appropriate to ED.…”
Section: Materials/scalesmentioning
confidence: 99%